2020
DOI: 10.1186/s12934-020-1297-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a food-grade recombinant Lactobacillus plantarum with surface displayed AMA1 and EtMIC2 proteins of Eimeria tenella in broiler chickens

Abstract: Background: Avian coccidiosis posts a severe threat to poultry production. In addition to commercial attenuated vaccines, other strategies to combat coccidiosis are urgently needed. Lactobacillus plantarum has been frequently used for expression of foreign proteins as an oral vaccine delivery system using traditional erythromycin resistance gene (erm). However, antibiotic selection markers were often used during protein expression and they pose a risk of transferring antibiotic resistance genes to the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…EtAMA1 and EtIMP1 expressed and delivered in a live recombinant bacterial Lactococcus lactis vaccine resulted in reductions in oocyst output and lesion score (31,32). Similarly, EtAMA1 and EtMIC2 co-expressed in Lactobacillus plantarum and delivered as an oral vaccine reduced oocyst output and lesion score following challenge (33). As noted for most recombinant antigen-based vaccines for Eimeria (reviewed in ( 27)), our yeast-based vaccine reduced parasite replication but did not completely prevent parasite development and shedding.…”
Section: Discussionsupporting
confidence: 51%
“…EtAMA1 and EtIMP1 expressed and delivered in a live recombinant bacterial Lactococcus lactis vaccine resulted in reductions in oocyst output and lesion score (31,32). Similarly, EtAMA1 and EtMIC2 co-expressed in Lactobacillus plantarum and delivered as an oral vaccine reduced oocyst output and lesion score following challenge (33). As noted for most recombinant antigen-based vaccines for Eimeria (reviewed in ( 27)), our yeast-based vaccine reduced parasite replication but did not completely prevent parasite development and shedding.…”
Section: Discussionsupporting
confidence: 51%
“…L. johnsonii La1 (NCC533) reduces active trophozoite of Giardia intestinalis strain WB and infection duration in Meriones unguiculatus (286). Recombinant L. plantarum NC8 (containing Eimeria tenella protein) induced a higher percentage of a T-cell subset (CD3 + , CD4 + , and CD8 + ) and antibody levels, provided protection against E. tenella infection in chickens, and reduced lesion, cecum damage, and oocyst shedding (270). L. salivarius, L. johnsonii, and S. cerevisiae provided protection against Eimeria infection in chickens; reduced oocyst count, improved weight gain and FCR, and stimulated the immune response with higher antibodies (IgM and IgG) titer and lymphoproliferative response (271).…”
Section: Probiotics and Parasitic Diseasesmentioning
confidence: 99%
“…In recent years, several studies have shown that recombinant vaccines in combination with novel adjuvants may offer a stronger mucosal immunity that stimulates both innate and acquired (humoral and cell-mediated) immune responses against several Eimeria strains [ 30 , 31 , 32 , 33 , 34 , 35 ]. The delivery system of recombinant or subunit vaccine candidates, using eukaryote or prokaryote vectors for feed or water administration application have shown optimistic and realistic results [ 36 , 37 , 38 , 39 , 40 ]. Some of these novel vaccines not only provide antigenic diversity, but cost of production and welfare issues are significantly reduced or eliminated [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these secreted proteins are trafficked to the parasite surface and beyond via the secretory microneme (MIC) organelles, such as AMA1, IMP1, MIC1, MIC2, MIC3, micronemal protein 4 (MIC4), and micronemal protein 5 (MIC5) [ 3 , 4 , 5 , 16 , 30 , 39 , 50 ]. Several of these proteins were identified in our blots based on their homologous protein mass.…”
Section: Discussionmentioning
confidence: 99%